1999
DOI: 10.1007/s002329900517
|View full text |Cite
|
Sign up to set email alerts
|

Thermoreception of Paramecium: Different Ca 2+ Channels Were Activated by Heating and Cooling

Abstract: A Paramecium cell responded to heat and cold stimuli, exhibiting increased frequency of directional changes in its swimming behavior. The increase in the frequency of directional changes was maintained during heating, but was transient during cooling. Although variations were large, as expected with this type of electrophysiological recording, results consistently showed a sustained depolarization of deciliated cells in response to heating. Depolarizations were also consistently observed upon cooling. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Our previous results have also implicated NO in the morphine effect by NADPHdiaphorase cytochemistry [1]. It has been postulated that several NO-sensitive targets, including guanylyl cyclase, potassium channels and voltage gated calcium channels [21,22,23,24,25] are stimulated in invertebrates. Other studies using the ciliate protozoan Stentor have demonstrated that these types of microorganisms express a G protein-mediated response to morphine when stimulated mechanically [26].…”
Section: Discussionmentioning
confidence: 85%
“…Our previous results have also implicated NO in the morphine effect by NADPHdiaphorase cytochemistry [1]. It has been postulated that several NO-sensitive targets, including guanylyl cyclase, potassium channels and voltage gated calcium channels [21,22,23,24,25] are stimulated in invertebrates. Other studies using the ciliate protozoan Stentor have demonstrated that these types of microorganisms express a G protein-mediated response to morphine when stimulated mechanically [26].…”
Section: Discussionmentioning
confidence: 85%
“…The sensing of heat stress requires two cysteine residues (C35 and C105), localized within or nearby the HSF1 DNA binding domain, that are required for disulfide bond formation and HSF1 activation in response to heat stress [41][42][43][44][45]. In addition, ion channel activities reflect the temperature applied [68][69][70][71]. Activities of ion channels such as Na + /K + and Ca 2+ flux of mammals are highly sensitive to the change in ambient temperatures and thus suggested to be a kind of thermoreceptor or thermosensor that is involved in the perception of temperature [70].…”
Section: Thermodynamics Of Biomolecules and Heat Sensingmentioning
confidence: 99%
“…However, there is no indication that these TRPC Ca 2þ channels can function as thermosensors. Other channels reported as thermosensors (but not belonging to the TRP family) are heat-activated and cold-activated Ca 2þ channels in the ciliate Paramecium, each with a different ion selectivity [34], a heatactivated K þ channel in sponges [35], and a heat-activated background channel (KCNK2 or TREK-1) in the peripheral sensory neurons and central hypothalamic neurons [36].…”
Section: Introductionmentioning
confidence: 99%